PESAN DAKWAH DALAM ADAT PEUTRON ANEUK - Diana, Nur; Nurjana, Nurjanah (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Custom and Islamic law in Aceh society are two components that can not be separated. Both are likened to two sides of a coin so that in every order of life Aceh society’s life will always be based on Sharia law, including in terms of customary practices. Peutron aneuk custom is one of the customs that is still very common in Aceh, but actually this tradition has no proposition regarding the implementation of either in the Al-Qur’an or Al-Hadith. So the purpose of this study is to find out if there are any da'wah messages contained in it. This research is qualitative-descriptive with content analysis method and applied Saussure semiotic theory. The data has been collected through observation, interviews and documentation. The results showed that harmonization between custom and Islam in Aceh society had developed in various aspects of human life. Although there is no detailed Islamic proporsition in peutron aneuk’s tradition, but in every procession still contains of Islamic sharia values. There are many preaching messages contained in both of the hablumminallah worship and hablumminannas.